The Tuol Sleng Archives and the Cambodian Genocide - Adam, Dawne (Archivaria, 1998)
The purposes of this paper are, first of all, to describe how the Khmer Rouge documented the genocide they committed against their fellow Cambodians, with particular emphasis on the records created, used, and stored at the Tuol Sleng Incarceration Centre; secondly, to describe the bureaucracy the Khmer Rouge created that supported their documentation activities; thirdly, to suggest some reasons why they documented their activities so extensively; and finally, to describe the disposition of their records and the uses to which they are now being put. The paper concludes with a discussion of the importance of the Tuol Sleng archives to the Cambodian people’s and international community’s pursuit of justice. RÉSUMÉ Les objectifs de cet article sont de présenter, en premier lieu, comment les Khmers Rouges ont documenté le génocide qu’ils ont perpétré envers leurs concitoyens cambodgiens en mettant plus particulièrement l’accent sur les documents créés, utilisés et entreposés au centre de détention de Tuol Sleng; deuxièmement, de décrirela bureaucratie créée par les Khmers Rouges pour soutenir leur travail de documentation; troisièmement, de suggérer quelques raisons expliquant pourquoi ils ont documenté leurs activités de manière si étendue; enfin, de présenter le processus de disposition des documents et les usages actuels des archives. L’article se termine sur une discussion de l’importance du dépôt de Tuol Sleng pour les Cambodgiens et la communauté internationale dans leur quête respective de justice.